Development and Validation of Reverse-phase High-performance Liquid Chromatography Method for Estimation of Citicoline Sodium in Bulk and Dosage Form - MARADIYA, H. K. (Medknow Publications & Media Pvt Ltd, 2013)
A simple, accurate, precise and sensitive reverse-phase high-performance liquid chromatography method for the determination of citicoline sodium has been developed and validated. Drug was resolved on a C18 column (Phenomenex Luna, 250×4.6 mm, 10μ), utilizing mobile phase of potassium dihydrogen phosphate buffer and acetonitrile in a ratio of 30:70. Mobile phase was delivered at the flow rate of 1.0 ml/min and detection was carried out at 272 nm. Separation was completed within 2.22 min. Calibration curve was linear with good correlation coefficient (R(2)=0.999) over a concentration range 10-60 μg/ml. Recovery was between 98.84 and 101.76%. Method was found to be reproducible with relative standard deviation for intra and interday precision of <2.0% over the said concentration range. The method was successfully applied to the determination of the citicoline sodium, it can be very useful and an alternate to performing the stability studies.